The Role of Nano Sized Particles to Treat Cancer - Saroj, Kumari Sushma; Vidyarthi , Sanjeev Kumar; Singh , Hari Mohan Prasad (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Nanoparticle technology is a new scientific research method to develop efficient drug delivery to cure various types of cancers. Combinations of anticancer drugs with different polymers are used in the formulation of nanoparticles. The particle size can be analyzed by using a particle size analyzer; morphological characters will observe by using a Scanning Electron Microscope and the potential of particles can be determined by using a zero potential analyzer. Polymorphic and compatible structures of a drug and polymer were determined with Differential Scanning Calorimetry and Fourier Transmission Infrared. By using nanoparticles, the drug shows better absorption, bioavailability, and systemic action.